Ethnic inequalities in obesity among children and adults in the UK: a systematic review of the literature. - El-Sayed, A; Scarborough, P; Galea, S (2011)
Ethnic minority groups are growing as a proportion of the British population. Although disparate, literature suggests inequalities in obesity risk within and among ethnic minority groups relative to Caucasians in the UK. We summarize and appraise the existing peer-reviewed literature about the prevalence and determinants of obesity among ethnic minority groups relative to Caucasians among children and adults in the UK. There was no consensus about obesity prevalence relative to Caucasians among South Asian or Black children or among South Asian adults relative to Caucasians. Black adults generally had higher risk for obesity than Caucasians. Both Chinese children and adults had lower risk for obesity than Caucasians. Few studies have considered differences in the aetiology of obesity by ethnicity. The lack of consensus regarding obesity risk among large ethnic minority groups relative to Caucasians in the UK, and the paucity of studies concerned with differences in obesity aetiology by ethnicity warrant further research in this area. Certain obesity metrics may bias obesity prevalence among particular ethnic groups relative to Caucasians. We summarize key methodological limitations to the current literature and suggest avenues for future research.